KEPENTINGAN QATAR MENGAMBIL ALIH KLUB PARIS SAINT GERMAIN FC MELALUI QATAR INVESTMENT AUTHORITY - Fantoni, Aulia Ilham; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study describe about Qatar interests took over Paris Saint Germains through Sovereign Wealth Fund (SWF) name is Qatar Investment Authorithy.The sources of this research were obtained through literature reviews, books, websites, and others. The source of analysis is qualitative methods. This study uses the level of analysis of the nation state, liberalism perspective considers that war is only a small part of existing reality. The liberalists hope international relation are understood throughly and not forget that cooperation between countries is one of themain things. Qatar is the country with the second largest LNG producers in the world. To replace future income and realize the Qatar National Vision 2030 Qatar invested heavily in the hotels and sport sector through Qatar Investment Authorithy with one of them by taking over Paris Saint Germains which one is the big club and strategic location at Paris.   Key Words: Paris Saint Germains, Qatar Investment Authority, Sovereign Wealth Fund.